Communal Religious Education in a Multicultural Indonesian Church - Jeniffer Wowor (Asosiasi Teolog Indonesia, 2020)
The reality of diversity is an integral part of Gereja Protestan di Indonesia bagian Barat (The Protestant Church in Western Indonesia, abbreviated as GPIB). This contextual plurality is the church’s wealth, which should make an essential contribution to its ministry. However, a singular challenge that arises in light of that diversity relates to the strong emphasis on “church unity”—which should be a supportive element—thus contributing to problems with the church’s ministry and pedagogy. How is this so? Given that centralized efforts to promote unity correlate closely with the imposition of rules that dominate and determine Christian religious education in the church, this article asserts the necessity of communal identity for an ongoingly diverse reality; communal identity, in other words, must not be destroyed in the name of promoting unity. The argument unfolds in three stages, entailing (1) a summary of the current context of the GPIB and problems it faces, (2) an academic study of the objectives of Christian religious education, to be considered in the context of the GPIB, and (3) a rationale for setting these objectives. Through these three stages, the communal vision is expected to contribute to the church’s ministry and education in the midst of the congregation and the whole Indonesian society with its multicultural context.